Walkaway : a novel - Doctorow, Cory (Tor, 2017)
"Hubert, Seth, and their ultra-rich heiress friend Natalie are getting a little old to hang out at the "Communist parties," techno-raveups in abandoned industrial spaces, full of insta-printed drugs and toys. And Natalie was finished, years ago, with her overcontrolling zillionaire dad. And now that anyone can manufacture food, clothing, shelter with equipment comparable to a computer printer, there seems to be little reason to stick with the world of rules and jobs. So, like hundreds of thousands of others in the mid-21st century, the three of them...walk away. Mind you, it's still dangerous out there. Much of the countryside is wrecked by climate change, and predators are with us always. Yet when the initial pioneer walkaways flourish, more people join them. Then the walkaways discover the one thing the ultra-rich have never been able to buy: how to beat death. Now it's war--a war that will turn the world upside down" -- provided by publisher.